Die Studies of Six Greek Baktrian and Indo-Greek Kings - Lerner, Jeffrey D. (Anabasis. Studia Classica et Orientalia, 2018)
Olivier Bordeaux has successfully produced a significant contribution to the field of Hellenistic Central Asian numismatics, Les Grecs en Inde. The work stems from the author’s thesis written under the direction of Osmund Bopearachchi. In some respects, the book under review acts as a welcomed revision to Bopearachchi’s 1991 opus. There is little doubt that this work will be regarded as foundational and a standard reference for years to come.